INTEGRASI NILAI-NILAI KEISLAMAN DALAM TRADISI SAKAI SAMBAIAN PADA MASYARAKAT LAMPUNG : STUDI LIVING QUR’AN - Khairil Anwar; Nasrulloh Nasrulloh (STIT Sunan Giri Bima, 2024)
This research is aimed at describing the Sakai Sambaian tradition that exists in Lampung society and to look at the religious arguments regarding musawah wa mahabbah that are implied in the Sakai Sambaian tradition. The research method used in this research is qualitative with a phenomenological type. In the phenomenological concept in this research, the living Qur'an theory is used to describe the religious postulates implicit in the Sakai Sambaian tradition. The result of this study is that the Sakai Sambaian tradition carried out by the people of Lampung is carried out when a resident holds a big event such as the demolition of fields or rice fields, the construction of houses and weddings. Then the religious postulates that show the values to Islam in the tradition are implied in the Sakai Sambaian activity which has 3 activity patterns, namely; 1) Sakai Sambaian is done sincerely without any strings attached, 2) Sakai Sambaian is done by all citizens regardless of ethnicity, race and religion and 3) Sakai Sambaian is done as proof of gratitude for the blessings given.